Long-term BTX-A effects on bi-articular muscle: Higher passive force, limited length range of active force production and unchanged intermuscular interactions - AKDENİZ DOĞAN, ZEYNEP DENİZ (ELSEVIER SCI LTD, 2021)
Botulinum toxin type-A (BTX-A) is commonly used for spasticity management aiming at reducing joint stiffness and increasing joint range of motion in CP patients. However, previous animal studies showed acutely increased passive forces and a narrower length range of active force exertion (lrange) for muscles exposed. BTX-A can spread affecting mechanics of several muscles in a compartment, but it was shown acutely to diminish epimuscular myofascial force transmission (EMFT). Yet, our understanding of these effects in the long-term is limited and they need to be tested in a bi-articular muscle. The goal was to test the following hypotheses in a long-term rat model: exposure to BTX-A (i) has no effects on lrange and passive forces of bi-articular extensor digitorum longus (EDL) muscle and (ii) diminishes EMFT. Male Wistar rats were divided into two groups: BTX-A and control (0.1 units of BTX-A or only saline was injected into the tibialis anterior). Isometric proximal and distal EDL forces were measured simultaneously, one-month post-injection. Proximally and distally lengthening the muscle showed that BTX-A causes a significantly narrower lrange (by 14.7% distally and 32.2% proximally) and significantly increased passive muscle forces (over 2-fold both distally and proximally). Altering muscle position at constant length showed that BTX-A does not change EMFT. The findings reject both hypotheses showing that long-term exposure to BTX-A compromises bi-articular muscle's contribution to motion for both joints and the muscle's mechanical interaction with the surroundings remains unaffected. These effects which may compromise long-term spasticity management should be studied in CP patients.
Keywords: Botulinum toxin type A long-term effects; Bi-articular muscle; Muscle passive force; Muscle active force; Intermuscular mechanical interactions; Epimuscular myofascial force transmission; TOXIN TYPE-A; EXTRAMUSCULAR MYOFASCIAL FORCE; BOTULINUM-TOXIN; SPASTIC EQUINUS; CEREBRAL-PALSY; CHILDREN; TRANSMISSION; RAT; COMPARTMENT; NEUROTOXIN